2021
DOI: 10.1002/rhc3.12219
|View full text |Cite
|
Sign up to set email alerts
|

Trust in experts, not trust in national leadership, leads to greater uptake of recommended actions during the COVID‐19 pandemic

Abstract: Evidence suggests that people vary in their desire to undertake protective actions during a health emergency, and that trust in authorities may influence decision making. We sought to examine how the trust in health experts and trust in White House leadership during the COVID‐19 pandemic impacts individuals' decisions to adopt recommended protective actions such as mask‐wearing. A mediation analysis was conducted using cross‐sectional U.S. survey data collected between March 27 and 30, 2020, to elucidate how i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 79 publications
0
25
0
Order By: Relevance
“…However, trust can be classified into several types. Recent studies have suggested that trust in nongovernmental health experts could increase participants' acceptance of protective measures ( Ahluwalia et al, 2021 ). Future studies should investigate the effects of other trust dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…However, trust can be classified into several types. Recent studies have suggested that trust in nongovernmental health experts could increase participants' acceptance of protective measures ( Ahluwalia et al, 2021 ). Future studies should investigate the effects of other trust dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research during the COVID‐19 pandemic has shown that support for preventive health measures is much greater among individuals with more institutional trust (e.g. Ahluwalia et al, 2021 ; Lachapelle et al, 2021 ), providing an incentive to also study its merit in nutrition‐related health promotion efforts. Consequently, we hypothesize: Less ‐ educated individuals make less use of institutional nutrition information because they distrust institutions more (hypothesis 1).…”
Section: A Novel Explanation For Less‐educated Individuals’ Limited N...mentioning
confidence: 99%
“…Literature suggests that a complex interplay of factors influences the desire of people to undertake the recommended actions during a crisis, such as the sociodemographic characteristics, knowledge, personal responsibility, perception of personal risk or threat [99], and one's personal stance towards a scientific topic [5], among others. The above factors are tied to trust since information that is coming from trusted sources is more likely to be considered accurate and can influence one's willingness to adhere to the recommended measures [99]. Importantly, trust has been also found to be a predictor of compliance to protective measures [20][21][22][23][24][25][26][27][28].…”
Section: Compliance With Public Measuresmentioning
confidence: 99%